Identifying direct targets of transcription factor Rfx2 that coordinate ciliogenesis and cell movement - Kwon, Taejoon (Genom Data, 2014)
Recently, using the frog Xenopus laevis as a model system, we showed that the transcription factor Rfx2 coordinates many genes involved in ciliogenesis and cell movement in multiciliated cells (Chung et al., 2014). To our knowledge, it was the first paper to utilize the genomic resources, including genome sequences and interim gene annotations, from the ongoing X. laevis genome project. For researchers who are interested in the application of genomics and systems biology approaches in Xenopus studies, here we provide additional details about our dataset (NCBI GEO accession number GSE50593) and describe how we analyzed RNA-seq and ChIP-seq data to identify direct targets of Rfx2.